2018
DOI: 10.1002/jaal.933
|View full text |Cite
|
Sign up to set email alerts
|

Building Bridges From Classrooms to Networked Publics: Helping Students Write for the Audience They Want

Abstract: Research about adolescents sharing creative writing in interest‐driven online communities has suggested that teachers can play important roles in helping young writers realize the potential of online spaces. Framed by sociocultural notions of new literacies and a conceptual framework theorizing the rhetorical situation when sharing writing in networked publics, this instrumental case study examined the design and implementation of a high school elective course supporting students to critically analyze and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(34 reference statements)
0
5
0
2
Order By: Relevance
“…olika sätt att använda skrivande, på fritiden har till stor del fokuserat på vad och i vilka syften ungdomar skriver (t.ex. Grover m.fl., 2016;Lammers & Van Alstyne, 2019;Vaughan, 2020). På fritiden kan exempelvis skrivandet vara ett sätt att knyta och upprätthålla sociala kontakter, men även ingå som en central del i ungdomarnas kreativa och identitetsskapande utveckling (se t.ex.…”
Section: Inledningunclassified
See 1 more Smart Citation
“…olika sätt att använda skrivande, på fritiden har till stor del fokuserat på vad och i vilka syften ungdomar skriver (t.ex. Grover m.fl., 2016;Lammers & Van Alstyne, 2019;Vaughan, 2020). På fritiden kan exempelvis skrivandet vara ett sätt att knyta och upprätthålla sociala kontakter, men även ingå som en central del i ungdomarnas kreativa och identitetsskapande utveckling (se t.ex.…”
Section: Inledningunclassified
“…och fanfiction(Curwood m.fl., 2013;Lammers & Van Alstyne, 2019).Skrivhändelser i form av sms verkar däremot vara desto vanligare i ungdomars vardag. I en svensk enkätstudie av 300 gymnasieelever genomförd avBellander (2006) framkom att 39 procent av flickorna och 20 procent av pojkarna skickade sms dagligen, samt ytterligare 40 respektive 35 procent skickade sms varje vecka.…”
unclassified
“…The digital nature of multimodal compositions makes them particularly sharable both inside and out side classrooms, giving students opportunities to com pose for audiences beyond their teachers (Hutchison & Colwell, 2014;Lammers & Marsh, 2015;Nash, 2018). In openly networked (Ito et al, 2013) classrooms in which teachers have connected their classroom spaces to on line affinity spaces, students shared their writing with wider audiences (Lammers & Van Alstyne, 2019). Other research has revealed that although students were able to share their writing with wider, online audiences, sometimes receiving constructive feedback, they pre ferred feedback from their classroom peers with whom they felt less vulnerable (Magnifico et al, 2018).…”
Section: Multimodality and Participationmentioning
confidence: 99%
“…Online affinity space writing research has consistently offered implications for teachers to implement similar practices (e.g., Magnifico, Lammers, & Fields, 2018) with a reshaped notion of affinity spaces suited to traditional classroom settings (Bommarito, 2014). Yet, few studies have documented teachers actually implementing these practices (Lammers & Van Alstyne, 2019; Marsh, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation